BS IEC 63098-2 Ed.1.0. Transmitting equipment for radiocommunication. radio-over-fibre technologies and their performance standard. Part 2. Radio over fibre based fronthaul network for railway communication system (14th September 2020) - British Standards Institution,
No abstract available